Reducing excess mortality due to chronic disease in people with severe mental illness: meta-review of health interventions - Baxter, AJ; Harris, MG; Khatib, Y; Brugha, TS; Bien, H; Bhui, K (Cambridge University Press, 2018)
Background People with severe mental illness (SMI) have high rates of chronic disease and premature death.